INFORMATION TECHNOLOGIES IN AN EDUCATIONAL PROCESS AND LEARNING FOREIGN LANGUAGES (Academicia Globe: Inderscience Research, 2021)
This article presents important information about the development of IT in the modern world. In addition, it promotes the beneficial aspects of information technology in the current educational systems (especially the educational process of language learning). In addition, in this article also includes the impact of the efforts of the first President Islam Karimov and the signed documents in the modern Uzbek education system.